Thorvald Solberg papers - Solberg, Thorvald, 1852-1949.
Correspondence, memoranda, speeches, writings, reports, drafts of copyright legislation, articles, notes, bibliographical material, genealogical and biographical material, printed matter, photographs, and other papers relating chiefly to Solberg's duties as register of copyrights, Library of Congress Copyright Office, and to his efforts to protect literary and artistic rights in America and abroad. Subjects include the Berne Convention for the Protection of Literary and Artistic Works of 1896, the revision of the convention in 1908, and the congress in Rome, Italy, leading to its 1928 revision; book production of the Balearic Islands, Spain; the writings of Ludwig Salvator, Archduke of Austria; writings in English on Scandinavia; Solberg's travels in Europe; and family affairs. Correspondents include William Archer, R.R. Bowker, Richard Crosby DeWolf, Willard Fiske, Wendell Phillips Garrison, J.C.M. Hanson, Marie Maschner, Bernard Shaw, and Solberg family members.
Register of copyrights (1897-1930), Library of Congress Copyright Office.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection related to the Library of Congress Archives.
Keywords: Archer, William, -- 1856-1924 -- Correspondence; Bowker, R. R. -- 1848-1933 -- Correspondence; DeWolf, Richard C. -- Correspondence; Fiske, Willard, -- 1831-1904 -- Correspondence; Garrison, Wendell Phillips, -- 1840-1907 -- Correspondence; Hanson, J. C. M. -- 1864-1943 -- Correspondence; Ludwig Salvator, -- Archduke of Austria, -- 1847-1915.; Maschner, Marie -- Correspondence; Shaw, Bernard, -- 1856-1950 -- Correspondence; Solberg family; Solberg family -- Correspondence; Solberg family -- Genealogy; Library of Congress -- Officials and employees; Library of Congress. -- Copyright Office; Berne Convention for the Protection of Literary and Artistic Works -- (1886); Berne Convention for the Protection of Literary and Artistic Works -- (1908); Berne Convention for the Protection of Literary and Artistic Works -- (1928); Book industries and trade -- Spain -- Balearic Islands; Copyright; Copyright -- United States; Copyright, International; Copyright, International -- Congresses; Genealogy; Europe -- Description and travel; Scandinavia -- In literature; Public officials